Trauma Bay Disposition of Infants and Young Children With Mild Traumatic Brain Injury and Positive Head Imaging. Issue 11 (November 2019) - Noje, Corina; Jackson, Eric M.; Nasr, Isam W.; Costabile, Philomena M.; Cerullo, Marcelo; Hoops, Katherine; Rasmussen, Lindsey; Henderson, Eric; Ziegfeld, Susan; Puett, Lisa; Robertson, Courtney L.
Abstract : Objectives: To describe the disposition of infants and young children with isolated mild traumatic brain injury and neuroimaging findings evaluated at a level 1 pediatric trauma center, and identify factors associated with their need for ICU admission. Design: Retrospective cohort. Setting: Single center. Patients: Children less than or equal to 4 years old with mild traumatic brain injury (Glasgow Coma Scale 13–15) and neuroimaging findings evaluated between January 1, 2013, and December 31, 2015. Polytrauma victims and patients requiring intubation or vasoactive infusions preadmission were excluded. Interventions: None. Measurements and Main Results: Two-hundred ten children (median age/weight/Glasgow Coma Scale: 6 mo/7.5 kg/15) met inclusion criteria. Most neuroimaging showed skull fractures with extra-axial hemorrhage/no midline shift (30%), nondisplaced skull fractures (28%), and intracranial hemorrhage without fractures/midline shift (19%). Trauma bay disposition included ICU (48%), ward (38%), intermediate care unit and home (7% each). Overall, 1% required intubation, 4.3% seizure management, and 4.3% neurosurgical procedures; 15% were diagnosed with nonaccidental trauma. None of the ward/intermediate care unit patients were transferred to ICU. Median ICU/hospital length of stay was 2 days. Most patients (99%) were discharged home without neurologic deficits. The ICU subgroup included all patients with midline shift, 62% patients with intracranial hemorrhage, and 20% patients with skull fractures. Across these imaging subtypes, the only clinical predictor of ICU admission was trauma bay Glasgow Coma Scale less than 15 ( p = 0.018 for intracranial hemorrhage; p < 0.001 for skull fractures). A minority of ICU patients (18/100) required neurocritical care and/or neurosurgical interventions; risk factors included neurologic deficit, loss of consciousness/seizures, and extra-axial hemorrhage (especially epidural hematoma). Conclusions: Nearly half of our cohort was briefly monitored in the ICU (with disposition mostly explained by trauma bay imaging, rather than clinical findings); however, less than 10% required ICU-specific interventions. Although ICU could be used for close neuromonitoring to prevent further neurologic injury, additional research should explore if less conservative approaches may preserve patient safety while optimizing healthcare resource utilization. Abstract : Supplemental Digital Content is available in the text.